Conversion of colonoscopy to flexible sigmoidoscopy: an unintended consequence of quality measurement in endoscopy. Issue 3 (11th December 2015) - Thompson, Chris; Ismail, Tariq; Radley, Simon; Walt, Robert; Ward, Stephen Thomas
Abstract : Objective: To quantify the proportion of requests for colonoscopy that are performed as flexible sigmoidoscopy and documented reasons for this in ordinary UK hospital practice. To determine the effect these requests have on colonoscopy completion rate if they are included in the denominator of the calculated rate by individual endoscopist. Design: Retrospective study of 22 months flexible sigmoidoscopy practice at a major UK teaching hospital. All flexible sigmoidoscopies performed had their associated request form examined. Setting: UK NHS University Hospital. Patients: All patients receiving outpatient flexible sigmoidoscopy from January 2013 to October 2014 with no exclusions. Intervention: Conversion of colonoscopy to flexible sigmoidoscopy. Main outcome measures: Conversion of colonoscopy to flexible sigmoidoscopy, reason for conversion and adjusted colonoscopy completion rate. Results: 71 of the 3526 flexible sigmoidoscopies performed (2.0%), representing 71 of 5905 colonoscopy requests (1.2%). Conversion reason was noted only in 26 (37%) of converted cases. Adjustment of colonoscopy completion rate to include conversions pushed four of our unit's 22 endoscopists below the UK national 90% standard. Conclusions: Conversion to flexible sigmoidoscopy occurs in 1.2% of patients originally booked for colonoscopy. The reason for this conversion is often unqualified and may be inappropriate. Conversion can affect the colonoscopy completion rate, and therefore, should be included in endoscopists' overall performance statistics.